(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The objective of this study was to determined the improvement of the students’ speaking ability after having applied a small talk strategy. Small Talk was the communicative teaching technique which gave more opportunities to the students to express their idea in the target language. In this research, the researcher used a pre-experimental method with one group pre-test and post-test to collect the data. The samples of this study were the second grade of SMP Muhammadiyah 3 Bontoala Makassar that consisted of 35 students. The results of the research showed that the implementation of small talk strategy in the teaching and learning process of speaking had been effective to improve the students’ speaking ability, it can be seen the mean score of pre-test and post-test in speaking test dealing with vocabulary, the data showed that the mean score of pre-test was 58.86% and the post-test was 77.43%. And then, the Improvement in pronunciation, the score of pre-test was 53.71% and the score of post-test was 75.71%.